2020
DOI: 10.3390/molecules26010165
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Inhibitory Activity of a Synthetic Defensin Derived from Barley Endosperm against Common Food Spoilage Yeast

Abstract: In the food industry, food spoilage is a real issue that can lead to a significant amount of waste. Although current preservation techniques are being applied to reduce the occurrence of spoilage microorganisms, the problem persists. Food spoilage yeast are part of this dilemma, with common spoilers such as Zygosaccharomyces, Kluyveromyces, Debaryomyces and Saccharomyces frequently encountered. Antimicrobial peptides derived from plants have risen in popularity due to their ability to reduce spoilage. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In addition to antibacterial activity, we also found that the new peptide was no toxic to human cells (Figures 8 and 9), a decrease in cell viability occurred only at 125 µM, which is a much higher concentration than that at which peptides exert antibacterial effects. The hemolytic activity of a peptide can generally be linked to its cytotoxicity and to its ability to cause harmful effects on eukaryotic cells 54,55 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to antibacterial activity, we also found that the new peptide was no toxic to human cells (Figures 8 and 9), a decrease in cell viability occurred only at 125 µM, which is a much higher concentration than that at which peptides exert antibacterial effects. The hemolytic activity of a peptide can generally be linked to its cytotoxicity and to its ability to cause harmful effects on eukaryotic cells 54,55 …”
Section: Discussionmentioning
confidence: 99%
“…The release of haemoglobin from defibrinated sheep erythrocytes caused by the presence of the protein was calculated following the protocol outlined by Shwaiki [ 16 ]. Briefly, a 4% red blood cell (Oxoid™, Oxoid Ireland c/o Fannin Healthcare, Ireland) solution was incubated for 1 h at 37 °C with 50, 100 and 200 μg/ml concentrations of the antifungal protein.…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxicity of the antifungal protein was tested by measuring cell viability using a MTT cell viability kit (Cell proliferation Kit I MTT, Sigma Aldrich, MO, USA). The protocol was performed as described by Shwaiki [ 16 ]. Human colonic cells, Caco-2 cells (ECACC) were maintained and passaged in Dulbecco's Modified Eagle Media (DMEM) supplemented with 1% non-essential amino acids and 10% Fetal Bovine Serum (FBS).…”
Section: Methodsmentioning
confidence: 99%
“…The discovered ability of AMPs to prevent the appearance of biofilms [ 12 , 80 , 86 ], and their antiviral [ 67 , 80 , 81 ], antifungal [ 87 , 88 , 89 ], antiprotozoal [ 90 ], and antitumor [ 91 , 92 , 93 , 94 ] effects, as well as their immunomodulatory activity, serves as a serious basis for the development of modern medicines [ 95 , 96 ].…”
Section: Antimicrobial Activitymentioning
confidence: 99%